Penguatan literasi digital dan kepemimpinan pelatih olahraga sekolah untuk mendukung pembinaan atlet abad ke-21 di kota mataram, provinsi nusa tenggara barat - Herman Syah; M. Ary Irawan; Zul Anwar (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2026)
School sports coaches play a strategic role in developing student-athletes capable of meeting the demands of twenty-first-century competencies. However, a preliminary needs assessment involving Physical Education teachers and extracurricular sports coaches in Mataram City, West Nusa Tenggara Province, revealed limited utilization of digital technology for training program design, athlete performance evaluation, team communication, and training data management. Furthermore, coaches' leadership competencies, including collaboration, motivation, decision-making, and digital communication, require continuous improvement to enhance athlete development. This community service program aimed to strengthen digital literacy and leadership competencies among school sports coaches through training, workshops, hands-on practice, and mentoring. The program employed a Participatory Action Research (PAR) approach consisting of needs assessment, program planning, implementation, mentoring, and evaluation stages. The participants consisted of 35 Physical Education teachers and extracurricular sports coaches from junior and senior secondary schools in Mataram City. Training materials included digital literacy, cloud-based applications for training management, digital media utilization in athlete development, transformational leadership, effective communication, and technology-based training program design. Evaluation results indicated significant improvements in participants' digital literacy and coaching leadership competencies, as reflected in higher post-test scores, increased proficiency in utilizing digital applications, and the successful development of technology-based training programs in participating schools. Overall, the program contributed positively to improving coaches' competencies in managing athlete development through more effective, collaborative, adaptive, and technology-oriented coaching practices aligned with the demands of twenty-first-century sports development.